Internet-based, therapist-guided, cognitive–behavioural therapy for body dysmorphic disorder with global eligibility for inclusion: an uncontrolled pilot study. Issue 3 (23rd March 2019) - Gentile, Andrew J; La Lima, Christopher; Flygare, Oskar; Enander, Jesper; Wilhelm, Sabine; Mataix-Cols, David; Rück, Christian
Abstract : Objectives: Cognitive–behavioural therapy (CBT) has been shown to be an effective treatment for body dysmorphic disorder (BDD), but access to treatment around the world is limited. One way to increase access is to administer CBT remotely via the internet. This study represents the first effort to remotely deliver a therapist-supported, internet-based CBT treatment with no restrictions on enrolment based on geographical location, and it aims to assess whether this treatment can be delivered safely across international borders, with outcomes comparable to previous BDD-NET trials. Design: Uncontrolled clinical trial. Participants: Patients (n=32) in nine different countries were recruited primarily through internet advertisements. Intervention: BDD-NET is a 12-week treatment, consisting of eight treatment modules previously shown to be effective in a Swedish version. Setting: Therapists based at a single, secondary care centre in Sweden provided active guidance and feedback throughout the treatment via asynchronous electronic messages. Main outcome measure: The clinician-administered Yale-Brown Obsessive Compulsive Scale for BDD (BDD-YBOCS). Symptom severity was assessed pretreatment, mid-treatment (6 weeks), post-treatment and at the 3-month follow-up. Results: There were significant improvements on BDD-YBOCS scores (F(3, 71.63)=31.79, p<0.001), that were maintained at 3-month follow-up. Mean differences from baseline in BDD-YBOCS scores were −8.12 (week 6), –12.63 (post-treatment) and −11.71 (3-month follow-up). 47% and 50% of participants were considered treatment responders at post-treatment and 3-month follow-up, respectively. Additionally, remission rates were 28% at post-treatment and 44% at 3-month follow-up. The treatment was also deemed acceptable by patients. Conclusions: The results suggest that BDD-NET can be safely and effectively delivered across international borders to a culturally diverse sample. Larger scale randomised controlled trials with more participants from non-Western cultures are warranted to further validate the cross-cultural generalisability of this treatment. Trial registration number: NCT03517384 .